The Role of Spirituality and Religiosity in Subjective Well-Being of Individuals With Different Religious Status - Villani, Daniela; Sorgente, Angela; Iannello, Paola; Antonietti, Alessandro (Frontiers in Psychology, 2019)
Spirituality and religiosity have found to be positive predictors of subjective well-being, even if results are not altogether consistent across studies. This mixed evidence are probably due to the inadequate operationalization of the constructs as well as the neglect of the moderation effect that the individuals’ religious status can have on the relation between spirituality/religiosity and subjective well-being. The current study aimed to investigate the relation of spirituality and religiosity with subjective well-being (operationalized both as life satisfaction and balance between positive and negative affect) and to test whether differences exist according to individuals’ religious status (religious, non-religious, and uncertain). Data were collected from 267 Italian adults aged 18-77 (M=36.68; SD=15.13), mainly women (59.9%). In order to test the role of spirituality (operationalized as Purpose, Innerness, Interconnection, and Transcendence) and religiosity (operationalized as three dimensions of the religious identity: Commitment, In-depth Exploration, and Reconsideration of Commitment) had on subjective well-being, two path analysis models were run, one for each predictor. To test the invariance of two models across the individuals’ religious status, two multi-group models were run. The models concerning spirituality were tested on the entire sample, founding that spirituality had a positive impact on subjective well-being (except for the dimension of Interconnection) and that this relation is unaffected by the individual’s religious status. The models concerning religiosity were instead tested only on religious and uncertain, founding that the relation between religiosity and subjective well-being changes across religious status. In particular, the main difference we found was that religious identity commitment positively predicted satisfaction with life among religious, but not among uncertain individuals. Interpretation of results and their implications were discussed.